Global Media Sport Flows, Forms and Futures - Rowe, David (Globalizing Sport Studies, 2011)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. How has globalization impacted on sports media? What are the economic ramifications? And what is the future of sports media? In order to answer these questions, this book investigates the constituents, dimensions and implications of the flows of media sport from the Global West to the Global East, and in the reverse direction. At an historical moment when the relative stability of the Western media sport order is under challenge, it analyses a range of key structures, practices and issues whose ramifications extend far beyond the fields of play and national contexts in which sport events take place. The book will appraise and analyse the state of sports television, rise of new sports media, emergence of hybrid sport cultural forms, eruption of sport-related political controversies, scandals and power struggles, mutations of forms of global sport fandom, and projections of the future of global media sport. In bringing together the latest research from across a number of disciplines, this book offers an exciting contribution to the emerging field of global sports media.